Non-pharmacological Weight Loss Program in a Rural Community: Feasibility Study - Alea McClintock-Donahue (Rural Nurse Organization; Binghamton University, 2019)
Background Obesity is a complex health problem that affects over one-third of US adults. Obesity rates are higher in rural communities, which may not have the resources to address. A community-based non-pharmacological weight loss program was implemented to address the limitations of managing rural obesity, specifically cost and transportation. Methods A descriptive study was used to explore the feasibility of an 8-week non-pharmacological weight loss program that included nutrition and healthy lifestyle education for overweight or obese adult residents of a rural community in Western Maryland (n=23). Results The program was low-cost and had high participant satisfaction. Participants whom completed the program showed an increase in motivation to making lifestyle changes (p=0.0002); consumed fewer calories from fat (p=0.029); and had a small change in BMI (p=0.0389). The increase in physical activity minutes with program completion was not statistically significant (p=0.2285). Weather, family and work obligations were barriers to attendance. Conclusions This rural community-based weight loss program was feasible, addressed the barriers of cost and transportation, and can be adapted to meet the needs of other rural communities. Keywords: obesity, obesity intervention, rural, community, feasibility, non-pharmacological DOI: http://dx.doi.org/10.14574/ojrnhc.v19i2.516